CYBER RISKS IN THE FINANCIAL SECTOR IN THE CONTEXT OF DIGITAL TRANSFORMATION - PRYKHODKO, Borys (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article presents a comprehensive analysis of contemporary cyber threats to the financial sector, emphasizing their impact on the stability of financial institutions and payment systems. The study addresses the primary vectors of cyberattacks—phishing, DDoS, malware, targeted APT attacks, and insider threats. Drawing on the experiences of Ukrainian and international financial institutions, the paper identifies key principles for constructing cybersecurity systems, encompassing multi-layered protection, vulnerability management, proper authentication, and incident response planning. Special attention is devoted to artificial intelligence and machine learning as instruments for enhancing cyber resilience. The article also examines the potential for implementing blockchain and decentralized finance (DeFi) within the global financial landscape and the associated information security challenges. The significance of integrated cyber risk management within financial institutions’ broader operational risk management framework is underscored. Finally, practical recommendations are offered on optimizing security frameworks, adopting international standards, and bolstering intergovernmental coordination to ensure the financial sector’s long-term resilience in the face of digital transformation.